Seed producer-led marketing strategies: high-Impact, cost-effective strategies to drive demand for quality seed for cassava and sweetpotato - Edson, S.; Ogero, K. (2025)
This research brief presents evidence from a pilot initiative involving 20 cassava and sweetpotato seed producers across Tanzania’s Lake Zone (Mwanza, Geita, Shinyanga, Simiyu, Kagera, and Mara). The study tested various seed producer-led marketing approaches, including social networks, agricultural exhibitions, demonstration plots, stakeholder meetings, and promotional materials. Results revealed that social networks, stakeholder meetings, and demonstration plots had the highest return on investment (ROI) and lowest cost-effectiveness ratio (CER). Agricultural fairs and printed materials were costlier but improved long-term brand visibility. The brief recommends combining high-reach, low-cost tactics with targeted visibility investments to enhance sales, market reach, and profitability for seed producers of vegetatively propagated crops (VPCs).